COMPARATIVE ANALYSIS OF BIOCOMPATIBILITY CHARACTERISTICS OF BASE RESINS FOR REMOVABLE DENTURES - Ozhogan, Z.R.; Tytyk, V.M.; Ozhohan, P.Z.; Zaiats, O.R.; Viklyuk, I.V.; Ozhohan, R.Z.; Kyrylyuk, M.I. (World of Medicine and Biology, 2025)
We manufactured and studied samples of acrylic plastics Villacryl, Ftorax and elastic thermoplastic Acron. The relief of the surfaces of the samples was studied at different scale levels using digital optical microscopy (Carl Zess NU-2E optical microscope), micro-profilometry (Veeco DEKTAK 3030 profilometer) and atomic force microscopy (scanning probe microscope Bruker NanoScope IIIa Dimension 3000 TM). The wettability of surfaces at the macro level was characterized by measuring the wetting angle of a stationary drop. Samples of the elastic plastic Akron demonstrate the smallest wetting angle (WA) – 60.8°, which indicates good wettability, but have the highest surface roughness (14 nm). Acrylic plastics Villakryl and Ftorax, despite a smoother surface (8 and 10 nm), have a higher WA (65.1° and 83°), which indicates lower hydrophilicity due to the chemical composition of the surface. Elastic prosthetic plastics with their unique surface interaction profiles hold promise for specialized applications in partial removable dentures.
Keywords: absence of teeth; acrylic resin; elastic resin; biocompatibility; wetting angle; partial removable dentures